Дослідження часу простою автомобілів на митних пунктах пропуску при виконанні міжнародних перевезень вантажів - Немна, Тетяна; Свічинський, Станіслав (Видавництво Львівської політехніки, 2018)
The processes affecting the trucks’ standing time at customs chekpoints when making international cargo transportation between Ukraine and the countries of Commonwealth of Independent States are described. The standing time regularities are obtained on the basis of transportation processes observations.
Research of automobile standing time at customs chekpoints when making international cargo transportation
Keywords: 656.135.4